The Effects of Different Undergrowth Vegetation on the Types and Densities of Functional Ground-Dwelling Arthropods in Citrus Orchards - Inagaki, Hidehiro; Yuto, Saruta; Daiki, Yoto (Caraka Tani: Journal of Sustainable Agriculture, 2022)
In agricultural lands, citrus orchards, pest feeding and weed seed predation by ground-dwelling arthropods are essential ecosystem services. This research aims to investigate the effects of different undergrowth vegetation, including weed area, bare land, rattail fescue and white clover fields, on the types and densities of functional ground-dwelling arthropods in citrus orchards, using pitfall traps. The captured organisms included carnivorous beetles (Pheropsophus jessoensis, Chlaenius naeviger and Dolichus halensis), wolf spiders (Lycosidae sp.), earwigs (Anisolabididae sp.), house centipedes (Scutigeromorpha sp.), herbivorous ground beetles (Amara sp., Harpalinae sp.), crickets and millipedes. Furthermore, the population of the functional ground-dwelling arthropods was significantly increased by the presence of a live mulch, where a higher number was seen in the rattail fescue or white clover compared to the weed or bare land fields. The cover crops also affected the types of arthropods identified, with the rattail fescue field including more Pheropsophus jessoensis while the white clover had an elevated number of wolf spiders, earwigs and Amara sp. (a weed seed predator). This discovery indicates that the type of undergrowth vegetation plays an important role in enhancing functional biodiversity. The kind of pests and weeds that these arthropods are effective against, as well as the extent to which their densities can be decreased, is also unknown. Therefore, further research on the feeding habit and predation of these arthropods should be conducted.